Priorização da manutenção de superestrutura ferroviária através de programação por metas - Moura, Diogo Furtado de (2018)
Defining the proper maintenance strategy is an essential task for the railroad that seeks longevity in its business and seeks to achieve long-term goals, involving multiple, often immeasurable and conflicting objectives. This article presents a tool that allows prioritizing the maintenance of the railway superstructure based on a scenario of demand for maintenance of components and geometric, environmental and demographic characteristics that exist along the path of the track. Among the optimization techniques to aid in the decision-making process, Goal Programming was used to allow the existence of multiple objectives. The results showed that the proposed model allowed the prioritization of the goals defined as the most important and it proved useful in the presentation of scenarios that facilitate the choice of the superstructure maintenance sites.